DEVELOPMENT OF THE INTERNAL CORPORATE CONTROL UNDER CONDITIONS OF TAX MONITORING - Vanchukhina, Lubov; Galeeva, Nelly; Rogacheva, Anastasia; Rudneva, Yuliya; Shamonina, Tamara (Revista Inclusiones, 2020)
The relevance of the issue under study is conditioned by the fact that the Federal Tax Service of Russia promotes the concept of tax administration based on the enhanced information interaction with a taxpayer. In this respect, the necessity to adapt the internal control system to the conditions of the tax monitoring became pressing. The goal of the paper is to adapt the internal control system of the organization to a new form of the enhanced information interaction between the parties of tax relations. The leading approach to the study of this issue is a risk-oriented approach to delivery of the information concerning the internal control system and to use of the information by the tax authorities. As a consequence, there was presented a model of interaction of an economic entity with a tax authority with respect to the internal control system. The model is based on COSO methodology which will secure the reduction of risks of misstatement of tax liabilities of a taxpayer.